2017
DOI: 10.1002/bies.201700043
|View full text |Cite
|
Sign up to set email alerts
|

Offspring sex ratio in mammals and the Trivers‐Willard hypothesis: In pursuit of unambiguous evidence

Abstract: Can mammalian mothers adaptively control the sex of their offspring? The influential Trivers-Willard hypothesis (TWH) proposes that when maternal condition increases the fitness of sons more than that of daughters, the proportion of sons produced should increase with maternal condition. Studies of mammals, however, often fail to support this hypothesis. This article highlights recent advances, including studies on the assumptions of the TWH and physiological mechanisms for sex-ratio manipulation. Particular em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 124 publications
1
31
0
Order By: Relevance
“…Based on a study on lifetime reproductive success, Leimar (1996) suggested that under certain circumstances, high quality women can have a higher reproductive value than high quality men. Our results are in line with other studies (Douhard 2017;Ellis and Bonin 2002;Keller et al 2001;Kolk and Schnettler 2016;Kozieł and Ulijaszek 2001;Morita et al 2017), which did not find support for the TWH.…”
Section: Discussionsupporting
confidence: 92%
“…Based on a study on lifetime reproductive success, Leimar (1996) suggested that under certain circumstances, high quality women can have a higher reproductive value than high quality men. Our results are in line with other studies (Douhard 2017;Ellis and Bonin 2002;Keller et al 2001;Kolk and Schnettler 2016;Kozieł and Ulijaszek 2001;Morita et al 2017), which did not find support for the TWH.…”
Section: Discussionsupporting
confidence: 92%
“…The T-WH could be supported under the following three assumptions: (1) good maternal condition leads to good condition of her offspring; (2) one's good condition at child stage results in his/her good condition at adult stage; and (3) males compete for their mating and reproductive opportunities with each other, where those in better condition have higher reproductive success than individuals in worse condition. There exist numerous studies on the T-WH, but the results have been quite mixed (e.g., Douhard, 2017;West, 2009, see also Veller, Haig, & Nowak, 2016 for the T-WH on sex-biased parental investment).…”
Section: Introductionmentioning
confidence: 99%
“…In practice, demonstrating adaptive significance is not easy because fitness is often difficult to measure, especially in the wild. Furthermore, GCs and maternal GCs may be correlated with other physiological traits that are directly involved in adaptive manipulations of sex ratios [54]. The crossover patterns shown in Figure 2 have not yet been tested in studies investigating direct links between GCs and sex ratio.…”
Section: Adaptive Significancementioning
confidence: 99%